Ontogenetic changes in the expression of immune related genes in response to immunostimulants and resistance against white spot syndrome virus in Litopenaeus vannamei. (November 2017) - Rajkumar, T.; Taju, G.; Abdul Majeed, S.; Sinwan Sajid, M.; Santhosh Kumar, S.; Sivakumar, S.; Thamizhvanan, S.; Vimal, S.; Sahul Hameed, A.S.
Abstract: In recent years, researchers have focused on viral and plant immunostimulants which could have beneficial effects in disease prevention and control in shrimp culture. At present, the application of the recombinant VP28 protein (r-VP28) and herbal immunostimulant has been considered as a more effective approach to prevent white spot syndrome (WSS) by enhancing the immune response in shrimp. In the present study, expression of selected immune related genes in response to r-VP28 and herbal immunostimulant mix (HIM) were separately studied qualitatively and quantitatively by RT-PCR and real time PCR, respectively during ontogenetic development from nauplius to juvenile stage in Litopenaeus vannamei . The mRNA expression level of immune related genes such as anti-lipopolysaccharides (ALF), Lysozyme, cMnSOD, Crustin, Prophenoloxidase, Tumor necrosis factor receptor-associated factor 6 (TRAF6) and Haemocyanin were found to be up-regulated significantly in different ontogenetic development stages of shrimp fed with r-VP28 and HIM formulated diets. Relative percent survival (RPS) was determined in shrimp fed with immunostimulants formulated diets after oral challenge with WSSV. The survival of WSSV challenged shrimp was found to be higher in immunostimulants treated groups when compared to untreated group. The results of PCR, ELISA and real time PCR revealed the absence of WSSV in WSSV-challenged shrimp after 20 days of treatment with immunostimulants. Among these immunostimulants, HIM was found to be more effective when compared to r-VP28. After a survey of literature, we are of the opinion that this might be the first report on the expression of immune genes during ontogenetic development of L. vannamei in response to immunostimulants. Highlights: Expression of immune related genes during ontogenetic development in shrimp. Oral application of viral and herbal immunostimulants in shrimp. Immune response of shrimp to viral protein and herbal immunostimulant. Efficacy of viral protein and herbal immunostimulant to protect shrimp from WSSV infection.